THE ROLE OF BASEFLOW ON FLOOD DURATION (CASE STUDY: JAKARTA FLOODS 2008â2019) - Nurzaki Waliyatullah, Fadhilah
Historical flooding in Jakarta is an ongoing problem with significant economic, social and environmental impacts. Flooding in Jakarta can be caused by the overflow of the Ciliwung River. River flow consists of surface runoff and baseflow, where baseflow is an important component that contributes greatly to river flow. Separation of baseflow using the Recursive Digital Filter (RDF) method helps understand its contribution to flooding. This study examines the role of baseflow on flood duration in Jakarta during the period 2008–2019. The research data includes Water Level to calculate river discharge and rainfall to see its influence on baseflow discharge. Discharge calculations were conducted using the rating curve formula, and baseflow separation using the RDF method by Eckhardt (2005). Baseflow Index (BFI) was calculated to understand the contribution of baseflow during flood events. Analysis of floods during 2008–2019 showed that floods occurred frequently in January-March with the longest duration of 182 hours. Rainfall accumulated over 5 days before with a lag time of 1 day affects the baseflow discharge on the following day. High baseflow tends to prolong flood duration, as evidenced by the contribution of baseflow with a median Baseflow Index (BFI) value of 62.77% in long-duration floods, compared to 60.22% in short-duration floods, and 56.34% in medium-duration floods.